2021
DOI: 10.1186/s41100-021-00321-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported symptoms during dialysis: the effect of pre-dialysis extracellular water and change in extracellular water post-dialysis

Abstract: Background Quality of life for haemodialysis (HD) patients may be affected by symptoms during dialysis treatments, and patient groups have highlighted the need to improve post-dialysis fatigue and dialysis-related symptoms. As changes in extracellular water (ECW) may lead to cramps and other symptoms, we wished to determine whether there was an association between ECW and intra-dialytic symptoms. Methods We reviewed the hospital records of HD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…We found no difference in predialysis clinical status, medications, blood pressure, volume status, or pre-dialysis laboratory investigations, in keeping with several previous reports [4,[18][19][20]. Similarly, there were no statistically significant differences in the prescribed dialysis prescription between the two sessions, in terms of dialysate composition, dialyzer, peridialytic changes in blood pressure, or ultrafiltration rates, supporting earlier studies [4,[18][19][20][21]. However, longer recovery times were reported more frequently with high flux hemodialysis sessions compared to those with hemodiafiltration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found no difference in predialysis clinical status, medications, blood pressure, volume status, or pre-dialysis laboratory investigations, in keeping with several previous reports [4,[18][19][20]. Similarly, there were no statistically significant differences in the prescribed dialysis prescription between the two sessions, in terms of dialysate composition, dialyzer, peridialytic changes in blood pressure, or ultrafiltration rates, supporting earlier studies [4,[18][19][20][21]. However, longer recovery times were reported more frequently with high flux hemodialysis sessions compared to those with hemodiafiltration.…”
Section: Discussionsupporting
confidence: 91%
“…This relative difference in the change in ECW could potentially lead to a more pronounced effect in terms of reducing cerebral oxygenation in this older cohort of patients [34], and so possibly induce greater cytotoxic cerebral edema [35], consequently increasing the sensation of post-dialysis fatigue. This greater fall in ECW would support earlier reports that patients who start dialysis closer to their target weight, with lower ultrafiltration rates are more vulnerable to delayed post-dialysis recovery and fatigue [4,21], and equally excessive ultrafiltration rates could also reduce ECW and increase intercompartmental disequilibrium [11,18]. Although not statistically different, the median ultrafiltration rate adjusted for body weight, and percentage body weight change were slightly greater for those sessions with longer recovery times which would support a greater compartmental disequilibrium leading to patients reporting a longer recovery time.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Some studies have even reported that peridialytic symptoms were associated with lower UFRs 20 . This association with very low UFRs could possibly be explained in that fluid removal in patients attending for dialysis with little or no fluid to be removed, so closer to the postdialysis target weight could be at greater risk of developing symptomatic hypovolemia 31 . Other studies have highlighted that dialysis patients have greater self‐reported depression, 9 and those reporting more peridialytic symptoms and longer recovery times also reported greater psychological distress 5,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used the Fatigue questionnaire (FACIT-F) ( McKeaveney et al, 2021 ), a 40-item measure that assesses self-reported fatigue and its impact upon daily activities and function. However, the results of this questionnaire can be confounded by fatigue secondary to anaemia and volume overload ( Yoowannakul et al, 2021 ), and psychological distress. In our cohort distress thermometer scores were similar for both frail and non-frail patients, and previous studies have not shown an effect of psychological distress on muscle strength in dialysis patients ( Camilleri et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%